The anomalous alkalinization of the electrolyte during a slight anodic polarization of Mg: A different perspective. (1st March 2023) - Ortiz-Ozuna, A.; Godínez, F.A.; Genesca, J.; Montoya, R.
Abstract: To better understand several phenomena during the anodic polarization of Mg, a gel electrolyte (doped with phenolphthalein) was used to avoid the strong convective effects produced by H 2 evolution and reveal alkaline zones. Such a methodology is not new but is rarely used and this article does provide new insights about the Mg dissolution, when it is galvanically coupled to A A 7075 . It has been possible to show that the OH − ions generated during the Mg dissolution are locally neutralized into the electrolyte. On the other hand, the place (and its exceptional characteristics) where the Mg(OH) 2 compound is generated during the anodic dissolution of Mg was accurately identified.